Tantangan Penyelesaian Konflik Internasional yang Dilematik mengenai Hak Veto dalam Dewan Keamanan PBB (Studi kasus Palestina dengan Israel) - Wendra, Muhammad; Sutrisno, Andri (Journal of Contemporary Law Studies, 2024)
This research aims to explore and contribute to the understanding of the misuse of the veto power in resolutions for international conflict resolution. The focus is on describing the challenges arising from the use of the veto power in the UN Security Council, often prolonging conflicts without a definitive resolution. The research methodology employed is juridical normative with descriptive analysis, referring to provisions in the UN Charter and other reliable literature. The findings highlight that the abolition of the veto power in the UN Security Council could serve as a solution for more effective conflict resolution. Prolonged international conflicts result in significant losses, especially for civilians, while the UN, as the largest international organization, frequently fails to resolve these conflicts. The main issue lies in the rejection of resolutions by veto-wielding states, leading to the failure of these resolutions and the continuation of conflicts. Structural reforms within the UN are crucial to enhance its performance in conflict resolution to prevent further casualties. The unbridled use of the veto power, based on the geopolitical considerations of certain states, slows down the conflict resolution process. Additionally, the power disparity between veto-wielding states and other members contradicts the principle of sovereign equality enshrined in the UN Charter. Therefore, clear criteria must be established for the use of the veto power in peace resolutions to ensure that conflict resolution is not hindered by purely geopolitical interests.